Kajian Hukum Waris Islam Tentang Diyat Korban Meninggal Dunia Terhadap Ahli Waris Korban - Rahman, Irham; Rato, Dominikus; Dwi Anggono, Bayu; Mafazi, Agung (UNES Law Review, 2024)
The criminal law paradigm has begun to change since the emergence of the new Criminal Code (KUHP), where criminal punishment is emphasized not only as retaliation but also as recovery. Diyat punishment is one solution to restore victims. By giving property to the victim, you can make the victim's life easier financially. However, it is different from the diyat punishment for perpetrators of murder, not torture, which in this case has a perspective from the view of Islamic inheritance law. How is the diyat punishment given to the victim who is the heir of the murder victim from the perspective of Islamic inheritance law? This research uses normative legal research methods, namely by examining legal norms regarding diyat punishment from the perspective of Islamic inheritance law. Meanwhile, this research approach uses a statutory approach and a case approach related to diyat punishment. The results of research into the diyat punishment which should be the victim's right will be transferred to the victim's heirs considering that the victim has died as a result of murder. The concept of diyat punishment from the perspective of Islamic inheritance law is one of the appropriate solutions and is in accordance with the principles of the new Criminal Code.